Pengaruh Penerapan Sistem Informasi Manajemen Keuangan Daerah (SIMDA) Terhadap Kualitas Laporan Keuangan Di Badan Pengelolaan Keuangan Kabupaten Aceh Barat Daya - Siti Rahma Zahara; Ika Rahmadani (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
The Financial Management Agency of Aceh Barat Daya Regency is a government agency tasked with assisting the Regent in carrying out his government affairs in the financial sector under the authority of the region and assisting in providing assistance to the regional government. The purpose of this study is to examine whether the application of regional financial management information systems has an effect on the quality of financial reports at the Aceh Barat Daya District Financial Management Agency. The method in this study is a quantitative method using primary data. The sampling used is purposive sampling technique, the criteria used are employees who use SIMDA according to their duties and main tasks. The results of this study indicate that there are several influences between SIMDA on the quality of financial reports at the Financial Management Agency of Southwest Aceh Regency, namely there is a significant and positive influence between the two variables.